Institute at Still and Strange to Chinese Law, but Vitally He Needs’: Russian Notary in Manchuria (1904-1940-Ies) (1) - DRUZYAKA, Andrey Victorovich; BUYAROV, Dmitry Vladymirovich; KIREEV, Alexey Alexandrovich (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
In the article on the basis of previously unpublished documents from the Russian central and regional archives of the basic events in the history of establishment and development of notarial institutions in the Russian colonies in the northeast of China. The aim of the article is to analyse the historical conditions, the characteristics of the formation and the problems surrounding the formation, operation and transformation of Russian notary in Manchuria during the 1897 – 1940-ies. In the general context of events of regional history traces the main stages of its institutional development. The focus is on recreating the historical picture of the activities of public-law notary institute in Manchuria, to conclude that the actual value for the public and the administration of Harbin for the Russian diaspora and the entire urban society.